Osobennosti perifericeskogo krovoobrašcenija strelkov s poraženiem oporno-dvigatel'nogo apparata v sorevnovatel'nom periode godicnogo cikla sportivnoj podgotovki - Kalsina, V. V.; Zaytsev, P. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The paper presents an assessment of the nature of the peripheral blood circulation in athletes with lesions of the musculoskeletal system involved in bullet shooting. The features of the peripheral blood circulation of the upper limbs were studied at rest, before performing the load and after performing a standard exercise shooters. An assessment was made of the nature of the reactions of the arterial blood circulation, the state of tonus and elasticity of the vessels and the venous outflow.